KEDUDUKAN HAK ATAS TANAH MASYARAKAT HUKUM ADAT UNTUK KEPENTINGAN UMUM - Mebri, Jhon A (DiH: Jurnal Ilmu Hukum, 2017)
Land has a very important meaning in human life, because most of human life depends on the land. There is a close correlation between man and the land and there is no human in this world who does not need the land. The land is not only understood as an economic resource, but for others it sees the land as sacred and one of the indigenous peoples of Papua must preserve. So with the government policy to allocate land for public interest often conflict with the interest of indigenous people of Papua. Related to the procurement of land is regulated in Law No. 2 of 2012 on Land Procurement for Development for Public Interest. The focus of this research is how to recognize and regulate land rights of indigenous and tribal peoples for the public interest in Papua and how are the legal effects on customary land rights for indigenous and tribal peoples in Papua? By using normative research methods it can be concluded that the recognition and regulation of indigenous peoples' rights to land as customary rights in accordance with the provisions of the Basic Agrarian Law, the Law on Special Autonomy and Law No. 6 of 2014 on Villages, is recognized Of its existence and use in accordance with applicable provisions in indigenous and tribal peoples. However, in practice it is often not in accordance with the provisions in force in Indonesia, so as not to provide justice and legal certainty.The legal consequences of customary law community land acquisition for public interest are the form of indemnity for indigenous and tribal peoples through the agreed mechanism and the transfer of land rights of customary law community to the government.